An overview of Scirtidae (Coleoptera) described by Antoine Joseph Jean Solier (1792–1851) - Ruta, Rafał (Zootaxa, 2020)
In 1849 a French entomologist, Antoine Solier, described 11 species of Scirtidae collected in Chile by Claude Gay. Based on examination of type specimens deposited in the Museum national d’Histoire naturelle (MNHN) in Paris, 9 species: Contacyphon luteolineatus, C. parvus, C. tristis, Pseudomicrocara lunata, P. obliquata, P. torquata, and Elodes rousseli are briefly described with emphasis on male or female genitalia. Morphological details are illustrated. Type specimens of two species: Contacyphon maculatus and Elodes velutina were not found in the collection of MNHN. Two new synonyms were established: Contacyphon maculicornis (Solier, 1849) is a junior synonym of Pseudomicrocara patagonica (Curtis, 1838), and Cyphon testaceus Solier, 1849 is a junior synonym of Pseudomicrocara livida (Fabricius, 1775). Lectotypes of most species described by Solier are designated.